Mysticism, Meditation, and Monologue in Poemas del ser y del estar by Ernestina de Champourcin - Catherine G. Bellver (Studies in 20th & 21st Century Literature, 2012)
Between 1954 and 1972, Ernestina de Champourcin wrote a series of six books centering on her poetic persona’s quest for God and expressions of love toward Him. Poemas del ser y el estar is in many ways the culmination of her religious phase not only because it is the last in the series, but also because in it she reaches the serenity acquired when the search for God is over and the soul can dwell in the blissful state of illumination. Many have found implications of mysticism in her religious poetry. However, in spite of the evidence of a goal of transcendence and signs of the purgative and illuminative phases essential to the mystic journey, Champourcin cannot be rightly called a mystic, for she does not realize or aspire to total dissolution of the self in perfect union with God. She does separate herself from the social and the literary reality around her, but she never entirely blocks out the world of experience nor forfeits her sense of self. She writes not as a saint, but as a woman poet with an overriding preoccupation with God. Her poetic speaker turns away from the crowd, the material world, and the ego-centered self in order to look inward at the world of the spirit where she can quietly address the divine other and enjoy the splendor of His presence. For her, a spiritual joy is achieved when “ser” and “estar” commingle in time and place, existence announces essence, and divine presence illuminates her.
Keywords: Ernestina de Champourcin; religious poetry; Poemas del ser y el estar; mysticism; mediation; monologue; self-identity; time and space